The Relationship Between Body Composition, Anaerobic Performance and Sprint Ability of Amputee Soccer Players - Özkan, Ali (Akademia Wychowania Fizycznego w Katowicach, 2012)
The purpose of the present study was to investigate the relationship between body composition, anaerobic performance and sprint performance of amputee soccer players. Fifteen amputee soccer players participated in this study voluntarily. Subjects’ height, body weight, body mass index, body fat percentage (Jackson and Pollock formula) and somatotype characteristics (Heath-Carter system) were determined. The sprint performance at 10m, 20m and 30m was evaluated, whereas the counter movement jump (CMJ), relative CMJ (RCMJ), squat jump (SJ) and relative SJ (RSJ) tests were used for the determination of anaerobic performance. The results of the Pearson Product Moment correlation analysis indicated that body composition was significantly correlated with CMJ and SJ (p < 0.01), on the other hand, no measure of body composition was significantly related to the other component (p > 0.05). A significant correlation was found between CMJ, RCMJ, SJ, 10 m, 20 m and 30 m sprint performance (p < 0.05); whereas, in contrast, no measure of body composition was significantly related to the 10 m, 20 m and 30 m sprint performance (p > 0.05). In conclusion, the findings of the present study indicated that sprint performance was described as an essential factor in anaerobic performance whereas body composition and somatotype play a determinant role in anaerobic and sprint performance in amputee soccer players.